2001
DOI: 10.1007/s11906-001-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in pediatric hypertension?

Abstract: Research activities in the field of pediatric hypertension have been increasing in recent years, leading to important new findings in the epidemiology, diagnosis, and treatment of hypertension in children. This review summarizes recent work in these areas, focusing on the epidemic of obesity-related hypertension in children, advances in the drug therapy of childhood hypertension, and the increasing use of ambulatory blood pressure monitoring in evaluation of hypertensive children. Each of these three areas wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
2
19
0
1
Order By: Relevance
“…Obesity was the main independent risk factor for hypertension in the studied population and this has been shown in other studies of children (29,30). In regard to the effect of height and weight on blood pressure, most cross-sectional studies of children have shown a strong, positive correlation (29)(30)(31)(32). In a similar study in adolescents (24), a correlation was found between weight and systolic pressure in both boys (r=0.167, P≤0.01) and girls (r=0.112, P<0.01) (29).…”
Section: Discussionsupporting
confidence: 74%
“…Obesity was the main independent risk factor for hypertension in the studied population and this has been shown in other studies of children (29,30). In regard to the effect of height and weight on blood pressure, most cross-sectional studies of children have shown a strong, positive correlation (29)(30)(31)(32). In a similar study in adolescents (24), a correlation was found between weight and systolic pressure in both boys (r=0.167, P≤0.01) and girls (r=0.112, P<0.01) (29).…”
Section: Discussionsupporting
confidence: 74%
“…A number of findings on the history and physical examination may be indicative of the etiology of secondary hypertension. 34 Ambulatory BP readings may be useful in differentiating primary from secondary hypertension, as adolescents with secondary hypertension have been shown to manifest greater nocturnal SBP loads and greater daytime and nocturnal DBP loads than children with primary hypertension. 35 These patterns were highly specific for differentiating between essential (primary) and secondary types of hypertension.…”
Section: Use Of Abpm In Evaluation Of Secondary Hypertensionmentioning
confidence: 99%
“…Most reports on the prevalence of secondary hypertension come from studies undertaken at referral centers, which demonstrate a gradual shift towards a higher prevalence of primary hypertension, even in selected children [41]. The most common causes of hypertension differ according to the age of the children (Table 1).…”
Section: Etiological Classification Of Elevated Bpmentioning
confidence: 99%